2023
DOI: 10.1039/d2tb01980a
|View full text |Cite
|
Sign up to set email alerts
|

A dual aperture (mesoporous and macroporous) system loaded with cell-free fat extract to optimize bone regeneration microenvironment

Abstract: Injured bone regeneration requires complex and carefully orchestrated a series of events involving inflammation, angiogenesis, and osteogenesis. To mimic the developmental spatial structure, microenvironment of bone regeneration and the integration...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(59 reference statements)
1
2
0
Order By: Relevance
“…51−53 While it is the previously demonstrated pro-angiogenic effect of FE 10 that initiated our current effort for engineering pro-vasculogenic fibers, increasing evidence suggests that our FE, derived from healthy young women of different ages (22−35 years old) 10,54 in different locations of the body (e.g., abdomen, thighs, and upper arms) 11 with relatively stable concentrations of the major growth factors, has omnipotent biological functions in the treatment of different diseases, such as ischemic stroke, 43 osteoporosis, 55 osteoarthritis, 56 spinal cord injuries, 14 chronic wound healing, 13 reproductive related disorders, 38,57 and so on. With the multifaceted actions identified in FE, in tandem with its cell recruitment capability observed in our current study (Figures 4E,F and S1) and elsewhere, 44 the FE-PDA@PCL/GT fiber system will be well suitable for engineering 3D fibrous scaffolds 58,59 for in situ regeneration of different tissues. From the perspective of FE as a biological therapeutic agent, the advantages of high drug-loading efficiency and prolonged FE-releasing profile in the FE-PDA@PCL/GT fibers may offer new strategies for addressing the FE delivery issues.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…51−53 While it is the previously demonstrated pro-angiogenic effect of FE 10 that initiated our current effort for engineering pro-vasculogenic fibers, increasing evidence suggests that our FE, derived from healthy young women of different ages (22−35 years old) 10,54 in different locations of the body (e.g., abdomen, thighs, and upper arms) 11 with relatively stable concentrations of the major growth factors, has omnipotent biological functions in the treatment of different diseases, such as ischemic stroke, 43 osteoporosis, 55 osteoarthritis, 56 spinal cord injuries, 14 chronic wound healing, 13 reproductive related disorders, 38,57 and so on. With the multifaceted actions identified in FE, in tandem with its cell recruitment capability observed in our current study (Figures 4E,F and S1) and elsewhere, 44 the FE-PDA@PCL/GT fiber system will be well suitable for engineering 3D fibrous scaffolds 58,59 for in situ regeneration of different tissues. From the perspective of FE as a biological therapeutic agent, the advantages of high drug-loading efficiency and prolonged FE-releasing profile in the FE-PDA@PCL/GT fibers may offer new strategies for addressing the FE delivery issues.…”
Section: Discussionsupporting
confidence: 76%
“…This mode of delivery inevitably comes with the problems of low bioavailability and reduced efficacy, as the protein components in it have a short half-time and are vulnerable to degradation by enzymes in harsh application environments. Very recently, delivery strategies by having the FE blended into hydrogels , or encapsulated within nanoparticles , were attempted to sustain the FE release and augment its pro-angiogenic effect. In our case, the loading of FE was achieved by having the mussel-inspired PDA coated on the PCL/GT fiber surface to act as an underlayer for FE adsorption, as various biomolecules containing nucleophile groups (e.g., amines and thiols) can be covalently immobilized to the PDA-coating layer via the catechol groups .…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Qiu et al reported that CEFFE recruited osteoprogenitor and endothelial cells to support their neovascularization and osteogenesis during critical‐sized bone defect repair. [ 29 ] Jia et al found that CEFFE inhibited osteoarthritis progression via promoting cartilage regeneration and limiting joint inflammation. [ 30 ] These findings highlight the multifaceted impact of CEFFE on bone homeostasis.…”
Section: Discussionmentioning
confidence: 99%